Asymmetric Cryo-EM Structure of Anthrax Toxin Protective Antigen Pore with Lethal Factor N-Terminal Domain - Alexandra J. Machen; Narahari Akkaladevi; Caleb Trecazzi; Pierce T. O’Neil; Srayanta Mukherjee; Yifei Qi; Rebecca Dillard; Wonpil Im; Edward P. Gogol; Tommi A. White; Mark T. Fisher (Toxins, 2017)
The anthrax lethal toxin consists of protective antigen (PA) and lethal factor (LF). Understanding both the PA pore formation and LF translocation through the PA pore is crucial to mitigating and perhaps preventing anthrax disease. To better understand the interactions of the LF-PA engagement complex, the structure of the LFN-bound PA pore solubilized by a lipid nanodisc was examined using cryo-EM. CryoSPARC was used to rapidly sort particle populations of a heterogeneous sample preparation without imposing symmetry, resulting in a refined 17 Å PA pore structure with 3 LFN bound. At pH 7.5, the contributions from the three unstructured LFN lysine-rich tail regions do not occlude the Phe clamp opening. The open Phe clamp suggests that, in this translocation-compromised pH environment, the lysine-rich tails remain flexible and do not interact with the pore lumen region.